2015
DOI: 10.1007/s10878-015-9875-9
|View full text |Cite
|
Sign up to set email alerts
|

Computing unique maximum matchings in $$O(m)$$ O ( m ) time for König–Egerváry graphs and unicyclic graphs

Abstract: Let α (G) denote the maximum size of an independent set of vertices and µ (G) be the cardinality of a maximum matching in a graph G. A matching saturating all the vertices is a perfect matching.It is known that a maximum matching can be found in O(m • √ n) time for a graph with n vertices and m edges. Bartha [1] conjectured that a unique perfect matching, if it exists, can be found in O(m) time.In this paper we validate this conjecture for König-Egerváry graphs and unicylic graphs. We propose a variation of Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As mentioned in Sect. 1, both components have been studied earlier separately in Levit and Mandrescu (2016) and Krész (2006, 2009), respectively, and it has been observed that they preserve the number of perfect matchings in graphs. Moreover, leaf reduction (elimination) preserves the König deficiency as well.…”
Section: Reducing Graphsmentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned in Sect. 1, both components have been studied earlier separately in Levit and Mandrescu (2016) and Krész (2006, 2009), respectively, and it has been observed that they preserve the number of perfect matchings in graphs. Moreover, leaf reduction (elimination) preserves the König deficiency as well.…”
Section: Reducing Graphsmentioning
confidence: 99%
“…Leaf reduction by itself can be carried out by a straightforward linear-time (O(m)) algorithm. For a concrete implementation, see Levit and Mandrescu (2016). Thus, zero-leaf-reducibility of graphs is decidable in linear time.…”
Section: An Almost Linear-time Reduction Algorithmmentioning
confidence: 99%
See 3 more Smart Citations